2016
DOI: 10.4137/hpd.s40183
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Malaria Infections in an Endemic City of Honduras

Abstract: BACKGROUND:This study aimed at determining the prevalence of asymptomatic cases of malaria in Puerto Lempira, the municipality with the highest morbidity in Honduras. METHODS AND FINDINGS: Capillary blood was collected from 1,899 participants. All samples were analyzed through microscopy and a polymerase chain reaction (PCR) technique based on the amplification of species-specific repetitive sequences. The molecular approach was more sensitive than microscopy to detect asymptomatic infections (1.1% vs. 0.16%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Our data shows that while SMC is widely implemented with signi cantly high coverage rates reported in countries like Mali, a non-negligible proportion of children receiving SMC treatment (about 11.0%) are already carrying P. falciparum without any symptoms. Studies have shown that in malaria-endemic countries, there is a high prevalence of asymptomatic carriage of P. falciparum [9,[17][18][19][20][21] and that this parasitemia remains detectable in some children despite the administration of SP plus AQ during SMC [22].…”
Section: The Prevalence Of Asymptomatic Malaria Parasitemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Our data shows that while SMC is widely implemented with signi cantly high coverage rates reported in countries like Mali, a non-negligible proportion of children receiving SMC treatment (about 11.0%) are already carrying P. falciparum without any symptoms. Studies have shown that in malaria-endemic countries, there is a high prevalence of asymptomatic carriage of P. falciparum [9,[17][18][19][20][21] and that this parasitemia remains detectable in some children despite the administration of SP plus AQ during SMC [22].…”
Section: The Prevalence Of Asymptomatic Malaria Parasitemiamentioning
confidence: 99%
“…Asymptomatic carriage of parasites consists in the absence of clinical manifestations despite the presence of parasites in the blood. These individuals are very important for transmission because they constitute a reservoir of parasites [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%